Withdrawing monensin by the end of finishing period increases intake and changes ruminal fermentation patterns of cannulated Nellore cattle - Dellaqua, Joao Victor T. [UNESP] (2019)
Sao Paulo State Univ UNESP, Sch Vet Med & Anim Sci, Botucatu Campus, Botucatu, SP, Brazil